2019
DOI: 10.5871/jba/007s1.061
|View full text |Cite
|
Sign up to set email alerts
|

International supply chains: compliance and engagement with the Modern Slavery Act

Abstract: The UK Modern Slavery Act aims to reduce and eradicate various forms of exploitation and is in this respect in line with the Sustainability Development Goal (SDG) 8.7. Section 54 of the act focusses on modern slavery in the international supply chain of organisations and obligates organisations to report on the actions they have taken to identify and address exploitation vulnerabilities. In order to understand how effective the current provisions in the act are, we analyse how businesses in the fashion and tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 11 publications
2
67
0
6
Order By: Relevance
“…This is consistent with what other studies have found in their population samples (e.g. Voss et al, 2019).…”
Section: Non-compliancesupporting
confidence: 94%
“…This is consistent with what other studies have found in their population samples (e.g. Voss et al, 2019).…”
Section: Non-compliancesupporting
confidence: 94%
“…The interviews discussed above highlight working conditions that are consistent with modern slavery (Stevenson and Cole, 2018;Christ et al, 2019;Landman and Silverman, 2019;Mende, 2019;Pinheiro et al, 2019;Voss et al, 2019;Flynn and Walker, 2020): workers are expected to work long hours without overtime pay, they can be unfairly dismissed, and they must give gifts to their managers in order to keep their jobs. In some cases, managers impose fines and physically punish workers they are displeased with.…”
Section: Resultsmentioning
confidence: 99%
“…Servitude, in the form of forced labour, occurs when the victim does not consider themselves free to cease providing their labour or services or to leave their place or area of work because of the use of coercion, threats or deception labour (Franceschini, 2017;Stevenson and Cole, 2018;Mende, 2019). To be in a condition of servitude, the victim must also be significantly deprived of their personal freedom (Franceschini, 2017;Stevenson and Cole, 2018;Landman and Silverman, 2019;Mende, 2019;Pinheiro et al, 2019;Voss et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plausible deniability refers to a stance taken by businesses in which they only take responsibility for the technical requirements associated with conducting supplier due diligence, but do not take responsibility for ensuring that following these requirements actually lead to improvements in their performance. For example, though workers in the fashion and textile sectors are particularly vulnerable to exploitative labor conditions, "suppliers beyond the first tier are often not known to brands" and brand owners may not have "awareness of the ultimate source of their product" (Voss et al, 2019). Fashion brands that conduct due diligence or monitor for human rights only at first-tier suppliers may not have actual knowledge of slavery at secondor third-tier sub-contractors; hence, they may claim plausible deniability.…”
Section: Beyond Implausible and Plausible Deniability Toward Ethical mentioning
confidence: 99%